Differences in Transcriptional Activation by the Two Allelic (L162V Polymorphic) Variants of PPARα after Omega-3 Fatty Acids Treatment. (20th January 2009) - Rudkowska, Iwona; Verreault, Mélanie; Barbier, Olivier; Vohl, Marie-Claude
Abstract : Omega-3 fatty acids (FAs) have the potential to regulate gene expression via the peroxisome proliferator-activated receptorα (PPARα ); therefore, genetic variations in this gene may impact its transcriptional activity on target genes. It is hypothesized that the transcriptional activity by wild-type L162-PPARα is enhanced to a greater extent than the mutated variant (V162-PPARα ) in the presence of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) or a mixture of EPA:DHA. To examine the functional difference of the two allelic variants on receptor activity, transient co-transfections were performed in human hepatoma HepG2 cells activated with EPA, DHA and EPA:DHA mixtures. Results indicate that the addition of EPA or DHA demonstrate potential to increase the transcriptional activity by PPARα with respect to basal level in both variants. Yet, the EPA:DHA mixtures enhanced the transcriptional activity to a greater extent than individual FAs indicating possible additive effects of EPA and DHA. Additionally, the V162 allelic form of PPARα demonstrated consistently lower transcriptional activation when incubated with EPA, DHA or EPA:DHA mixtures than, the wild-type variant. In conclusion, both allelic variants of the PPARα L162V are activated by omega-3 FAs; however, the V162 allelic form displays a lower transcriptional activity than the wild-type variant.